Succeeding against the odds: Afro-Portuguese youth in Higher Education - Mateus, S.; Seabra, T.; Roldão, C.; Albuquerque, Adriana (Conferência Afroeuropeans: Black Cultures and Identities in Europe, 2017)
The significant presence of children of immigrants, in particular, with African origin, in schools in major Portuguese urban areas has made an important impact in sociological research in recent years, contributing to reinterpret old and new social inequalities. Little is known, however, about the educational paths of these students and their inclusion in higher education. There is a growing number of students with immigrant background in European Higher Education, showing the generational advancement and extension of the residence time of young people in the host or birth countries. Their access to higher education represents an important indicator of social inclusion and of impact of public policies. This emerging reality is the research focus of the project "Educational Paths of young Africans (PALOP) that access higher education". In this project we developed an exhaustive analysis of data from several official sources of statistical information, followed by a qualitative component that we address in this presentation - 17 biographical interviews conducted in 2015 to young Afro-Portuguese that did enrol in higher education, despite adverse socio-economic conditions. The analysis demonstrates and explores the institutional contexts, the social conditions of possibility, but also the individual experiences and strategies that shape counter-tendency educational paths. The presentation addresses the individual narratives and the specific challenges faced both in the life course and latter, in a social and ethnic reconfigured higher-education context. It aims to contribute to a better understanding of equity in access to higher education.